On Acosmic Realism - Végső, Roland (Filozofski vestnik, 2022)
In order to be able to raise the question of the “world” today in an effective way, we have to reactivate the Goethean categories of Weltliteratur and Weltschmerz for a critique of our own historical moment. We need to understand the phenomenon of Weltschmerz as a symptom of the impossibility of Weltliteratur. Going beyond the context of the original formulation of these categories, we could argue that something akin to the historical phenomenon of Weltschmerz emerges every time the ideological constitution of the world threatens to fail. Today, we live in an age of a generalised state of cultural disorientation that has produced its own Weltliteratur, which includes a wide range of discourses about the “world” – from officially endorsed theories of economic globalisation, to scientific treatises on the Anthropocene, environmental protest movements, philosophical pamphlets, all the way to world-historical conspiracy theories. Yet, an anxiety concerning the impossibility of world-formation in general is also recorded in these documents. In order to be able to capture our contemporary Weltschmerz, the article turns to the young Walter Benjamin’s suggestion that the task of this age is to produce an “objective” (rather than subjective) Weltschmerz. However, the most effective tools to conceptualise this objective Weltschmerz come from the traditions of philosophical acosmism. It is a notable philosophical development of our times that some elements of the acosmic tradition have recently resurfaced in speculative realism. Thus, speculative realism could be described as a possible site of our contemporary Weltschmerz: its acosmic metaphysics is repeatedly tamed by a mournful longing for the world.